“Belleza de Cristo”. Hitos para una estética cristológica en la obra de Olegario González de Cardedal (Teología, 2020)
The author presents the more important topics about Olegario González de Cardedal´s Christological Esthetics, which, based in Balthasar´s Theological Aesthetics, reconfiguresthe theological language to refer to the mystery of Jesus Christ in an estheticalperspective. It’s not about adapting Christology to Philosophical esthetics (thiswould only be a void estheticism) on the contrary, esthetics should be configured byChristology (Christological Esthetics). From this perspective, González de Cardedalproposes a new path in a programmatic way, so as to speak, think and hear the alwaysnew and always ancient mystery of Christ in the XXI Century. This is a facinating andatractive path to follow just like the glow of the Beauty of Jesus Christ.
Keywords: Olegario González de Cardedal; Christological Aesthetics; Beauty; Theology and poetry; Languages of God; Christology.